Thresholds of Abnormality Perception in Facial Esthetics among Laypersons and Dental Professionals: Profile Esthetics - Raed H. Alrbata; Ayham Kh. Alfaqih; Mohammad R. Almhaidat; Ahmad M. Al-Tarawneh (Hindawi Limited, 2020)
Aim. To find thresholds at which laypersons and dental professionals from Jordanian population perceive abnormalities in sagittal positioning of upper and lower jaws as a major determinant to facial profile esthetics. Materials and Methods. Using photo editing software, a baseline profile image of a young male was manipulated on a 2 mm incremental basis to move each of the upper and lower jaws backward and forward relative to true vertical line (TVL) at which four variables of maxillary and mandibular retrusion and protrusion were researched. A total of 120 participants divided equally into four groups of laypersons, general dental practitioners (GDPs), orthodontists, and oral and maxillofacial surgeons (OMFSs) rated the images using an analog scale of 100 mm long. The image that showed the first statistical difference compared to the baseline was considered as a threshold of abnormality. Results. Laypersons, GDPs, and OMFSs perceived the abnormality in the maxillary retrusion at −5 mm to TVL, while orthodontists defined that at −3 mm. All dental professionals perceived the abnormality in the maxillary protrusion at +1 mm to TVL while the layperson group at +3 mm. A threshold of −7 mm mandibular retrusion to TVL was abnormally perceived by all groups. All dental professionals realized the abnormality in the mandibular protrusion at 0 mm to TVL while the laypersons at +2 mm. Conclusion. These thresholds regarding profile esthetics may contribute to the process of establishing proper orthodontic treatment planning that suits the highest facial esthetic standards.